Uterine Transplant: A New Option to Restore Fertility - Valentin VARLAS; Roxana Georgiana BORS; Claudia MEHEDINTU; Monica CIRSTOIU (Modern Medicine)
The uterine transplant has been thought of as a treatment for women with absolute uterine factor infertility, allowing them to procreate, carry a pregnancy and give birth to genetic children not intended for lifelong use. In recent years, surgical techniques for donor sampling and uterine transplant have evolved, reducing complications that, along with proper immunosuppressive treatment, reduce the chances of rejection and improve obstetric outcomes, leading to increased live births. Pregnancy can be obtained by embryo transfer after ensuring that the graft is stable. Not being a life-saving transplant, after birth, the uterus can be kept for a new pregnancy, or a hysterectomy can be performed.